1998
DOI: 10.1063/1.1148584
|View full text |Cite
|
Sign up to set email alerts
|

Compact electron cyclotron resonance plasma source

Abstract: A compact electron cyclotron resonance plasma source has been built and is being investigated in view of ion and x-ray production. A method recently developed to deduce the energetic electron temperature parameter from the bremsstrahlung spectra emitted by the plasma is adapted to the present plasma case and shows that this temperature parameter can reach a dozen keV. We show that the high-energy electrons are localized on a ring in the mirror midplane by obtaining the image of the x-ray emitters on the chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 5 publications
0
18
0
2
Order By: Relevance
“…The high-energy component has a typical temperature of several tens of keVs [3] while the low-energy component has a much lower value, around 1 keV. Measured temperatures for the high energy electron population range from 5 to 13 keV for an ECRIS operated at 2.45 GHz [6,7], 40-60 keV for a CAPRICE source operated at 10 GHZ [13], and up to 100 keV for an ECRIS operated at 18 and 28 GHz [3,10]. As in the measurements cited above, our study is sensitive to the high-energy electron component due to our detection energy range of ∼ 20 − 120 keV.…”
Section: Evaluation Of the Plasma Characteristics A Bremsstrahlmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-energy component has a typical temperature of several tens of keVs [3] while the low-energy component has a much lower value, around 1 keV. Measured temperatures for the high energy electron population range from 5 to 13 keV for an ECRIS operated at 2.45 GHz [6,7], 40-60 keV for a CAPRICE source operated at 10 GHZ [13], and up to 100 keV for an ECRIS operated at 18 and 28 GHz [3,10]. As in the measurements cited above, our study is sensitive to the high-energy electron component due to our detection energy range of ∼ 20 − 120 keV.…”
Section: Evaluation Of the Plasma Characteristics A Bremsstrahlmentioning
confidence: 99%
“…The electron Bremsstrahlung spectra have been used for measuring electronic temperature in the ECRIS plasma [3][4][5][6][7][8][9][10], and high-resolution X-ray spectroscopy has been applied to characterize charge state distribution and electronic density [11][12][13][14]. Results on accurate X-ray spectroscopy, from Ref.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the a͒ Electronic mail: rb@igcar.ernet.in maximum x rays with energy 100 keV were observed at a distance of 14-18 mm from the axis. In the recent article by Gaudin et al, 25 the evidence of hot electrons leaking in the loss cone of magnetic mirror trap is studied. It should be noted that the ECR x-ray source is operated at a relatively higher pressure ͑7ϫ10 Ϫ5 Torr͒ and the Bremstrahlung spectrum is peaking at 12 keV and it is extending only up to 30 keV.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the ECR technique has been used for the production of x-rays. [22][23][24][25][26][27] The microwave source ͑frequency and power͒ used in ECR plasma x-ray source is similar to that of microwave ion source/plasma deposition systems. It is to be noted that the magnetic field configuration is different in ECR x-ray source compared to other ECR plasma devices and also, here the plasma is produced in a cavity.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] In recent years, x-ray source has been made based on ECR technique and the source is called ECR x-ray source. [11][12][13][14][15][16][17][18][19][20] In ECR x-ray source, electrons are accelerated continuously by matching the cyclotron frequency of the electrons to the microwave frequency ͑2.45 GHz͒. After gaining sufficient energy, these electrons collide with the target/cavity wall and produce bremsstrahlung x rays.…”
Section: Introductionmentioning
confidence: 99%